2011
DOI: 10.1142/s0219455411003975
|View full text |Cite
|
Sign up to set email alerts
|

Free Longitudinal Vibrations of Bimodular Beams: A Comparative Study

Abstract: In this paper, we consider the problem of the free longitudinal vibrations of a beam made of a bimodular material, i.e. an elastic material whose in-tension Young's modulus is a fraction of that under compression. After recalling the exact solutions for an infinite beam and for a beam with fixed ends calculated via the characteristics method, we apply high-resolution methods based on the finite-element approach to solve the nonlinear equation of the motion. In particular, we compare the exact solutions with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…(10), and boundary condition at the free end of the bar. The Hugoniot conditions (15) and (16) at all discontinuous wave fronts are also satisfied exactly.…”
Section: First Auxiliary Problem: Formation Of a Rigid Domain During mentioning
confidence: 83%
See 2 more Smart Citations
“…(10), and boundary condition at the free end of the bar. The Hugoniot conditions (15) and (16) at all discontinuous wave fronts are also satisfied exactly.…”
Section: First Auxiliary Problem: Formation Of a Rigid Domain During mentioning
confidence: 83%
“…To do this we check Eq. (16). First of all, it is easy to see that u u 0 before the shock wave, since the shock wave propagates faster thanthe sound velocity in the domain before the shock.…”
Section: Asymptotics For the Shock Wave Positionmentioning
confidence: 98%
See 1 more Smart Citation
“…В [39,40] различные варианты метода КНН применены для расчета напряженного состояния пластин из изотропных и анизо-тропных композиционных материалов. В [41] метод КНН приложен к решению за-дачи о продольных колебаниях бимодулярных балок, в [42] к решению уравнения Бюргерса и уравнения Кортевега-де Вриза-Бюргерса, в [27,43] к трехмерному моделированию лазерной сварки металлических пластин на адаптивных сетках в областях с криволинейной поверхностью.…”
Section: получена 15 августа 2016unclassified
“…To handle better this artefact, an adapted integration technique could be used. In [46] the authors suggested a collocation and least-squares (CLS) method, which over-performs other alternative integration methods in terms of accuracy and in simplicity of use. It is worth mentioning here that such a strongly non-linear hyperbolic problem with inherent shock waves and other discontinuities has to be treated using general energetic principles and so-called entropy conditions formulated in [47], notably the choice between possible solution has to follow the principle of the growth of entropy of particles crossing the shock front.…”
Section: Introductionmentioning
confidence: 99%